1991
DOI: 10.1007/bf01659066
|View full text |Cite
|
Sign up to set email alerts
|

Change of gastric liquid emptying after highly selective vagotomy and pyloric dilatation for patients with obstructing duodenal ulcer

Abstract: Gastric liquid emptying was studied in duodenal ulcer patients with and without stenosis before highly selective vagotomy (HSV) and 1 week, 3 months, and 1 year after. The test meal consisted of 1 mCi of 99m Technetium-diethylene penta-acetic acid (DTPA) in 500 ml of isotonic saline. The patients were divided into 2 groups: group 1 (16 cases) without clinical stenosis, who underwent HSV alone, served as control; group 2 (14 cases) with mild to moderate stenosis, who underwent HSV and transgastric dilatation to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1992
1992
2008
2008

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…12 -17 Previous studies on gastric emptying kinetics after HSV and combined procedures in patients with gastric outlet N Ozalp, MM Ozmen, B Zulfikaroglu et al Solid gastric emptying after highly selective vagotomy obstruction have produced conflicting results, due to differences in surgical techniques and tests used for assessment. 4,5,10,12,13,18,19 Following HSV, vagal innervation of the fundus is impaired, the intragastric pressure is increased and the emptying rate of liquids is accelerated. HSV preserves the antral innervation, so a solid gastric emptying test should be more accurate in evaluating the effects of drainage procedures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…12 -17 Previous studies on gastric emptying kinetics after HSV and combined procedures in patients with gastric outlet N Ozalp, MM Ozmen, B Zulfikaroglu et al Solid gastric emptying after highly selective vagotomy obstruction have produced conflicting results, due to differences in surgical techniques and tests used for assessment. 4,5,10,12,13,18,19 Following HSV, vagal innervation of the fundus is impaired, the intragastric pressure is increased and the emptying rate of liquids is accelerated. HSV preserves the antral innervation, so a solid gastric emptying test should be more accurate in evaluating the effects of drainage procedures.…”
Section: Discussionmentioning
confidence: 99%
“…It was consumed with 200 ml of milk within 10 min. 12,13 Once the meal was finished, gastric emptying scintigraphic studies were performed in a supine position using a gamma camera (SPX-6, Elscint, Hafia, Israel). Using anterior and posterior positions, data from the solid phase studies was acquired for 30 s per frame, at 5-min intervals, for a total of 90 min.…”
Section: Scintigraphymentioning
confidence: 99%
“…[28][29][30][31][32][33][34] In contrast, studies have shown that parietal cell vagotomy or highly selective vagotomy during Nissen fundoplication is not associated with increased side effects, morbidity, or mortality. [35][36][37] It may be that the difference in outcome may be attributed to the underlying disease rather than to the vagotomy.…”
Section: The Short Esophagusmentioning
confidence: 97%
“…It can be improved only by effective drainage. During the past 3 years HSV + D was rarely done in our patients because of the high incidence of delayed gastric emptying and poor clinical results [17].…”
Section: Discussionmentioning
confidence: 99%
“…During earlier years, the choice of dilatation was usually limited to mild fibrotic stenosis in order to avoid a duodenal rupture, and Jaboulay gastroduodenostomy was restricted to severe fibrotic stenosis where dilatation or pyloroplasty would be technically difficult. Dilatation was rarely done in our patients over the past 3 years, however, because of its poor results [17], and the use of Jaboulay gastroduodenostomy has not been restricted to severe fibrous stenosis.…”
Section: Hsv and Additional Proceduresmentioning
confidence: 91%